Bioactive substances of Colobanthus quitensis (Kunth) Bartl. from the Darboux and Lagotellerie Islands, western coast of Antarctic Peninsula - Ivannikov, R.; Anishchenko, V.; Poronnik, O.; Myryuta, G.; Miryuta, N.; Boyko, O.; Hrytsak, L.; Parnikoza, I. (Ukrainian Antarctic Journal, 2023)
The study aimed to investigate a wide spectrum of biologically active substances of an aboriginal Antarctic plant (Colobanthus quitensis) from the central and southern parts of its Antarctic part of general spread collected in 2020–2022. For 17 plants from 2 populations, we obtained extracts and analyzed them using high-throughput chromatography (HPLC). This was the first biochemical screening of plants from previously not investigated parts of this species’ range (Graham Coast and Marguerite Bay in the maritime Antarctic). The HPLC method characterized the overall metabolite pools and their separate components which could potentially have high biological activity. The most numerous groups of compounds included phenols and benzoic acids, hydroxybenzoic acids, hydroxycinnamic acids, flavonoids, apigenin glycosides, luteolin glycosides, tricin glycosides, flavonoid conjugates of the hydroxycinnamic acids, chlorophyll catabolites, carotenoids, terpenoids, and sterols. The quantitative content of the pearlwort’s metabolites depended on the population, probably due to the differences in the microhabitats. Meanwhile, such variability offers a wide selection of possible targets for biochemical screening. The Antarctic pearlwort is richer in some conjugates (such as flavonoid conjugates with the hydroxybenzoic acids) than the other Antarctic aboriginal plant – Antarctic hairgrass (Deschampsia antarctica). The determined substances might potentially be of great practical significance.